When the establishment of joint attention becomes problematic: how participants manage divergent and competing foci of attention - Stukenbrock, Anja; Balantani, Angeliki (Mobile eye tracking, 2025)
In the past decades, a substantial amount of research has studied how joint attention is collaboratively accomplished in social interaction. By contrast, divergent and competing foci of attention have remained largely unexplored. Our study investigates how participants establish, or refrain from establishing, joint attention in the face of attentional divergence and competition. When participants summon their co-participants’ attention on an object, the preferred response is to reorient and share attention. However, for various reasons, addressees may not always follow the invitation to share attention. One of the instances in which they may not (immediately) respond by reorienting is when they are themselves engrossed in something and prefer not to give it up for the sake of attention sharing. Using the methodological principles of Conversation Analysis and a corpus of naturally occurring interactions recorded with video cameras and mobile eye tracking glasses, we examine the use of deictics and embodied practices to invite joint attention in open states of talk when the co-participant’s attention is diverging. The recordings enable us to zoom in on how gaze (eye tracking data) and embodied orientation (data from external cameras) index and contribute to how sequences of divergent, competing, and joint attention unfold. Preliminary observations suggest, first, that the participants’ spatial configuration contributes to how the problem of competing foci of attention is handled, and second, that participants deploy different verbal and embodied practices to pursue joint attention in the face of competing sites of interest. These practices are sensitive to, and reflexively constitute the participants’ spatial configuration and range on a continuum from less to more response mobilising.